2018
DOI: 10.1038/s41598-018-26810-w
|View full text |Cite
|
Sign up to set email alerts
|

Audible Feedback Improves Internal Model Strength and Performance of Myoelectric Prosthesis Control

Abstract: Myoelectric prosthetic devices are commonly used to help upper limb amputees perform activities of daily living, however amputees still lack the sensory feedback required to facilitate reliable and precise control. Augmented feedback may play an important role in affecting both short-term performance, through real-time regulation, and long-term performance, through the development of stronger internal models. In this work, we investigate the potential tradeoff between controllers that enable better short-term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Nevertheless, it has been recently proposed to use a low-bandwidth discrete feedback communicating only contact events (Clemente et al, 2016). On the other side, some researchers tested approaches that increase the communication bandwidth, e.g., through the use of visual interfaces [e.g., augmented reality glasses (Clemente et al, 2017;Markovic et al, 2017)] or acoustic signals (Gonzalez et al, 2012;Shehata et al, 2018b). This can be also done through the tactile sense by employing electrodes that integrate a matrix of stimulating pads (Štrbac et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been recently proposed to use a low-bandwidth discrete feedback communicating only contact events (Clemente et al, 2016). On the other side, some researchers tested approaches that increase the communication bandwidth, e.g., through the use of visual interfaces [e.g., augmented reality glasses (Clemente et al, 2017;Markovic et al, 2017)] or acoustic signals (Gonzalez et al, 2012;Shehata et al, 2018b). This can be also done through the tactile sense by employing electrodes that integrate a matrix of stimulating pads (Štrbac et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown how well users will understand feedback presented simultaneously for multiple degrees of freedom. Subjective feedback during a previous study revealed subjects found it difficult to understand amplitude-modulated audio feedback for a two-degree-of-freedom virtual limb 34 , though other studies have demonstrated subjects are capable of understanding frequency-modulated audio feedback for two degrees of freedom 18 . Another option is to provide feedback through a different modality, such as vibrotactile, and encode active degree of freedom via stimulus location.…”
Section: Discussionmentioning
confidence: 96%
“…Audio feedback has been shown to strengthen a user’s internal model and improve their myoelectric prosthesis control performance 18 , however audio feedback may not be viable for daily use. Many myoelectric prosthesis users exploit sound and vibrations from the motors as a proxy for proprioceptive information 20,35 , but this motor noise may also diminish the perceived cosmesis of the limb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, prosthetic hand users rely on visual and incidental feedback for the closed-loop control of hand prosthesis (Markovic et al, 2018), as explicit feedback mechanisms are not prevalent in commercial prostheses (Cordella et al, 2016). Incidental feedback can be obtained from vibrations transmitted through the socket (Svensson et al, 2017), proprioceptive information from the muscles (Antfolk et al, 2013), sound from the motor (Markovic et al, 2018), or the reaction forces transmitted by the actuating cable in bodypowered prostheses (Shehata et al, 2018). Visual feedback has been the baseline feedback mechanism in prosthetic grasping exercises as it is the only feedback available naturally to all commercial hand prostheses (Saunders and Vijayakumar, 2011;Ninu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%